REVIEW: POTENSI EKSTRAK KAYU SECANG (Caesalpinia sappan L.) SEBAGAI ANTIDIABETES MELLITUS - Ashari Kurniawan Sarjono; Tukiran Tukiran (Unesa Journal of Chemistry, 2021)
Diabetes mellitus is an acute metabolic disorder with several causes with symptoms such as high blood sugar volume accompanied by disorders of carbohydrate, lipid and protein metabolism as a result of insulin function insufficiency. The use of synthetic hypoglycemic chemical drugs can cause some side effects and require relatively expensive costs, so traditional herbal medicine is preferred because it has less side effects and lower costs. Plants that can be used as traditional medicine are secang wood plants (Caesalpinia sappan L). Based on literature studies, compounds contained in the stem or wood part of secang contain flavonoid, tannins, gallic acid, resins, brasilein, α-phellandrene, oscimene, essential oils, resorcinol, and brasilin. It is known that tannic acid (tannins) has antioxidant activity and has an antidiabetic mellitus effects and the brazilin content of secang wood plays a very important role in reducing blood sugar levels. brazilin has three mechanisms of action in reducing blood sugar levels, namely reducing oxidative stress, inhibiting intestinal mucosa GLUT 2, and inhibiting phosphodiesterase. The antihyperglycemic activity of brazilin helps insulin work in the absorption of glucose from the bloodstream into adipose cells by increasing the translocation of glucose transport especially GLUT4. This shows that the extract from the secang wood plant has the potential as an antidiabetic mellitus. Keywords: Antidiabetic mellitus; Antioxidant; Hyperglycemic; Secang wood